2011
DOI: 10.1371/journal.pcbi.1002083
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Binding to P-Glycoprotein by Flexible Receptor Docking

Abstract: P-glycoprotein (P-gp) is an ATP-dependent transport protein that is selectively expressed at entry points of xenobiotics where, acting as an efflux pump, it prevents their entering sensitive organs. The protein also plays a key role in the absorption and blood-brain barrier penetration of many drugs, while its overexpression in cancer cells has been linked to multidrug resistance in tumors. The recent publication of the mouse P-gp crystal structure revealed a large and hydrophobic binding cavity with no clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 51 publications
(65 reference statements)
4
87
0
1
Order By: Relevance
“…We studied the active form of P-gp because of a need for conformational change to activate P-gp (28). The active P-gp was increased in GBM cells, acutely and chronically treated with temozolomide ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the active form of P-gp because of a need for conformational change to activate P-gp (28). The active P-gp was increased in GBM cells, acutely and chronically treated with temozolomide ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses had shown that docking studies performed by various approaches are reliable strategies to identify compounds that interact directly with ABCB1 [51][52][53]. From our previous studies, the docking scores obtained for a group of 54 substrates (including well-known substrates such as ivermectin and cyclosporine) had an average docking score of ≤ −12, like those we observed for enzastaurin in the 3G60 structure, while a group of 69 nonsubstrates had an average score of ~ −10 kcal/mol using MOE software and the same docking methodology [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Flexible receptor docking was performed using a multistage induced fit docking protocol (IFD) as described in detail previously. 20 Briefly, in the first stage, the van der Waals radii of protein and ligand are scaled by a factor of 0.5 and ligands are docked into the receptor using the default GlideSP mode. Next, Prime is used to predict and optimize selected protein side chains.…”
Section: ■ Methodsmentioning
confidence: 99%